A comparative study between immunohistochemistry, hematoxylin & eosin and geimsa stain for helicobacter pylori detection in chronic gastritis - DR.PRIYADHARSHINI.M,; DR.SINDU.V, (International Journal of Pharma and Bio Sciences, 2017)
Helicobacter pylorus (H.pylori) is now accepted as a major cause of chronic active antral gastritis. There is accumulating evidence to incriminate this microbe in the aetiology of duodenal ulcer and gastric carcinoma. The aim of this study was to ascertain the reliability of hematoxylin & eosin (H&E) and Geimsa stains in comparison with immunohistochemical (IHC) technique for the diagnosis of H.pylori.50 gastric biopsies were analysed in the present study. Sensitivity and specificity of Geimsa was 94% and 100% respectively. Sensitivity and specificity of H&E was found to be 70.59% and 100% respectively. Immunohistochemistry was positive in all cases in which H.pylori was detected by other methods. When the density of organism is low immunohistochemistry can be recommended for detection of H.pylori where the other two stains have low detection rate. It was concluded that Geimsa stain is less time consuming, relaible and readily available when compared to IHC technique